ALIENASI TOKOH UTAMA DALAM NOVEL POL KARYA PUTU WIJAYA - Efendi, Anwar (LITERA, 2005)
This research objective is to describe two things, namely (1) the manifestations of alienation and (2) characterization elements employed to describe human alienation in Pol, a novel by Putu Wijaya. These two things are related to the worldview adopted by Putu Wijaya as a writer in response to the sociohistorical condition in society. The source of the data in this study was Putu Wijaya's Pol (the first impression, 1987). The data were collected through reading and recording. The data analysis covered two aspects, namely (1) the structural aspect, and (2) the genetic aspect of the literary work, the writer's worldview. The validity was assessed through semantic validity and the reliability was assessed by reading and rereading (intrarater reliability). On the basis of the research findings and analysis, some inferences can be made. First, alienation in Pol on the basis of its manifestations can be classified into three categories, namely (a) loneliness, (b) spiritual emptiness, and (c) disappointment. Second, characters' alienation symptoms are expressed through characterization elements, comprising (a) the writer' s description of characters, (b) characters' thoughts, (c) characters' actions, and (d) minor characters' reactions to the main character. A literary work as a life model or an alternative world is always related to the real life. In the novel, Putu Wijaya posits himself as a photographer of the society's life.